FAKTOR - FAKTOR YANG BERPENGARUH PADA PEMILIHAN METODE AKUNTANSI PERSEDIAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PADA PERIODE 2012-2014 - Irfan Achmad Aditya, 12.05.52.0174; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2016)
The purpose of this study was to examine and analyze the factors wich have  effect ofthe selection of method of inventory accounting. The independent variable of this studyused company size, the variability of inventory and the variability of cost of goods sold. While the dependent variable in this study used the selection of method of inventory accounting which is agree with PSAK No.14 (2008) that is average method of inventory and FIFO method of inventory. The population in this research is manufacture companies that listed in Indonesia Stock Exchange in 2012 to 2014. Sampling was done using purposive sampling method. To test and analyze the influence between variables using logistic regression analysis. The results showed that the company size,the variability of inventory and the variability of cost of goods sold has no significant effect to the selection of method of inventory accounting.   Keywords: Company Size, The Variability of Inventory, The Variability of Cost of Goods Sold and The Selection of Method of Inventory Accounting